The Application of Hazard Analysis Critical Control Point(HACCP) in The Bakery Industry - Sena Fadjar Rochman; Agensy Nurmaydha; Gusti Randy Pratama (Universitas Darussalam Gontor, 2020)
Hazard Analysis and Critical Control Point (HACCP) is a system that identifies hazards to materials, processes, products and prevention ways by controlling the hazard. The D'rent Bakery & Cake was moving in the field of MSME, therefor must be a system that can guarantee and support food safety and quality assurance in the food industry, especially in MSME, namely by implementing the HACCP system. The purpose of this research is to identify the hazards and potential that may arise at every stage of the bread production process in D'rent Bakery & Cake in accordance of the HACCP system, analyzing the implementation of quality control and determining the CCP in the production process Bread at D'rent Bakery & Cake. This research was conducted at MSME the D'rent Bakery & Cake Ponorogo. Data collection i.e. primary data was obtained by observation and interviews. The data analysis technique wasdane by using 7 HACCP principles and 12 steps in the implementation of HACCP. This research identifies results in the process of making banana breadfrom raw materials to become products have same dangers reviewed, including the physical, chemical and biological. In the stage of the production process of banana bread there are 3 processes which are CPP namely the process of mixing bread dough there is a chemical hazard caused by materials contaminated with rust, the process of receiving eggs there is a biological hazard in the form of Salmonella bacteria and the cooling process there is a physical hazard in the form of dust and dirt. The advice from the researchers, were the implementation of HACCP in MSME the D'rent Bakery & Cake can help in fulfilling the quality requirements, increase the consumer confidence and give the vigilance of occurrence of contamination, therefore, they should be carried out internall audit and documented to fulfill the requirements of implementation of HACCP by related management